Teresa of Avila and Jonathan Edwards on Prayer and Spirituality - Liem Yoe Gie, Jonathan (Veritas : Jurnal Teologi dan Pelayanan, 2021)
Contemplative prayer has been a major source of contention in evangelical spirituality. Contemplative prayer is frequently mentioned as one apparent spiritual activity that is foreign to the scripture and Christian worldview and more resembling the New Age Movement and pantheistic Eastern religion by people who are skeptical of the mystical Christian tradition. This article will examine Teresa of Avila’s thought on mystical prayer, which is sometimes misinterpreted as a notion incompatible with evangelical theology of prayer. Hence, Teresa’s ideas of mystical prayer will be examined and compared with Jonathan Edwards’ concepts of prayer, which is considered to reflect evangelical theology of prayer. The comparison suggests that the contemplative, mystical prayer of Teresa is compatible with evangelical theology of prayer in its progress and purpose. Teresa and Edwards both understood prayer as an experience and progress that leads to the complete union with God, mediated by Christ and his words in scripture. This spiritual union with God will transform the devoted one with tremendous passion and strength to love and help others in their struggle and suffering. This study of Teresa’s thought of mystical prayer is expected to reinvigorate evangelical theology and praxis of prayer by learning from the rich spirituality of the Christian mystical tradition.